The DnaA AAA+ Domain His136 Residue Directs DnaB Replicative Helicase to the Unwound Region of the Replication Origin, oriC - Sakiyama, Yukari; Nishimura, Masahiro; Hayashi, Chihiro; Akama, Yusuke; Ozaki, Shogo; Katayama, Tsutomu (Frontiers in Microbiology, 2018)
Chromosomal replication initiation requires dynamic mechanisms in higher-order nucleoprotein complexes that are constructed at the origin of replication. In Escherichia coli, DnaA molecules construct functional oligomers at the origin oriC, enabling localized unwinding of oriC and stable binding of DnaB helicases via multiple domain I molecules of oriC-bound DnaA. DnaA-bound DnaB helicases are then loaded onto the unwound region of oriC for construction of a pair of replisomes for bidirectional replication. However, mechanisms of DnaB loading to the unwound oriC remain largely elusive. In this study, we determined that His136 of DnaA domain III has an important role in loading of DnaB helicases onto the unwound oriC. DnaA H136A mutant protein was impaired in replication initiation in vivo, and in DnaB loading to the unwound oriC in vitro, whereas the protein fully sustained activities for oriC unwinding and DnaA domain I-dependent stable binding between DnaA and DnaB. Functional and structural analyses supported the idea that transient weak interactions between DnaB helicase and DnaA His136 within specific protomers of DnaA oligomers direct DnaB to a region in close proximity to single stranded DNA at unwound oriC bound to DnaA domain III of the DnaA oligomer. The aromatic moiety of His136 is basically conserved at corresponding residues of eubacterial DnaA orthologs, implying that the guidance function of DnaB is common to all eubacterial species.